Perancangan Sistem Pembangkit Energi Angin Menggunakan Generator 12 V Untuk Pembangkit Listrik Tenaga Bayu - Ghazali, Dendi; Stefanie, Arnisa (Jurnal Ilmiah Wahana Pendidikan, 2024)
Electricity is a form of energy that is an essential need for almost all individuals in carrying out daily activities. An example of the use of electricity in everyday life is as a source of light, both inside the house and for street lighting. In the context of utilizing wind energy as an efficient alternative, one approach is through the use of generators. A generator is a device that has the ability to convert mechanical power into electrical energy. This innovation has renewable characteristics, so it can be applied in electricity generation through wind sources. The focus of this study is to identify the voltage and current generated by wind turbines to produce electrical energy. The experiment was conducted using a 15 Ω resistor at a wind speed of 2.6 m/s. The test results showed an average voltage value of 0.300V and a current of 0.099 mA at a wind speed of 2.6 m/s.